(untitled) (Research, Society and Development, 2026)
The objective of this study was to analyze the psychosocial impacts of feedback (praise and criticism) on employees’ behavior in an organizational environment, from the perspective of the Psychodynamics of Work. Methodologically, this is a qualitative and descriptive research, carried out through participant observation and field diary records. The results showed a clear behavioral dichotomy between the observed subjects: criticism perceived as punitive generated defense mechanisms and social isolation, physically manifested by the constant use of headphones and silence (Case "T.F."); in contrast, praise and technical support acted as catalysts for integration, expanding communication to areas of personal interest and improving customer service (Case "D."). It is concluded that interpersonal communication is not just an exchange of information, but a regulator of mental health at work, where positive validation strengthens psychological safety and productivity, while poorly managed criticism fosters withdrawal and the rupture of collaborative bonds.